K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

17 tháng 12 2017

a,x\(^2\)-2xy+5x-10y

=x(x-2y)+5(x-2y)

=(x-2y)(x+5)

b,x\(^2\)y+2xy\(^2\)+y\(^3\)

=x(x\(^2\)+2xy+y\(^2\))

=x(x+y)\(^2\)

c,x\(^2\)-(a+b)x+ab

=x\(^2\)-ax-bx+ab

=x(x-a)+b(x-a)

=(x-a)(x+b)

24 tháng 7 2016

a. 2xy - x2 - y2 + 16

=(2xy-x2-y2)+16 

=16-(x-y)2

=(4+x-y)(4-x+y)

b. x2 + x - 6

=x2+3x-2x-6

=x(x+3)-2(x+3)

=(x-2)(x+3)

c. x2 + 5x + 6

=x2+3x+2x+6

=x(x+3)+2(x+3)

=(x+2)(x+3)

23 tháng 11 2018

a) x4-9x2

(x2-3x)(x2+3x)

x2(x-3)(x+3)

23 tháng 11 2018

x2+y2+2xy-9

(x+y)2-32

(x+y-3)(x+y+3)

12 tháng 7 2019

a,\(xy+3x-7y-21\)

\(=x\left(y+3\right)-7\left(y+3\right)\)

\(=\left(y+3\right)\left(x-7\right)\)

12 tháng 7 2019

\(b,2xy-15-6x+5y\)

\(=\left(2xy-6x\right)+\left(-15+5y\right)\)

\(=2x\left(y-3\right)-5\left(3-y\right)\)

\(=2x\left(y-3\right)+5\left(y-3\right)\)

\(=\left(y-3\right)\left(2x+5\right)\)

2 tháng 8 2018

a) \(x^2-x-y^2-y\)

\(=\left(x^2-y^2\right)-\left(x+y\right)\)

\(=\left(x-y\right)\left(x+y\right)-\left(x+y\right)\)

\(=\left(x-y-1\right)\left(x+y\right)\)

b) \(x^2-2xy+y^2-z^2\)

\(=\left(x-y\right)^2-z^2\)

\(=\left(x-y-z\right)\left(x-y+z\right)\)

c) \(5x-5y+ax-ay\)

\(=5\left(x-y\right)+a\left(x-y\right)\)

\(=\left(5+a\right)\left(x-y\right)\)

10 tháng 10 2016

a)x2+2xy+y2-x-y-12

\(=\left(x+y\right)^2-\left(x+y\right)-12\)

Đặt \(t=x+y\) ta có:

\(t^2-t-12=t^2+3t-4t-12\)

\(=t\left(t+3\right)-4\left(t+3\right)\)

\(=\left(t-4\right)\left(t+3\right)\)

\(=\left(x+y-4\right)\left(x+y+3\right)\)

 

 

10 tháng 10 2016

b sai đề

7 tháng 10 2018

a) 2xy2 - 6x2y + 4xy

= 2xy.(y - 3x + 2)

b) x2 - y2 - 5x + 5y

= (x+y).(x-y) - 5.(x-y)

= (x-y).(x+y-5)

c) x2 - 4y2 - 1 + 4y

= x2 - (4y2 - 4y + 1)

= x2 - [ (2y)2 - 2.2.y.1 + 12 ]

= x2 - (2y-1)2

= (x+2y-1).(x-2y+1)

12 tháng 8 2015

a) x^4 - x^3 - x + 1 

= x^3 ( x - 1 ) - ( x- 1 )

= ( x^3 - 1 )(x - 1)

= ( x- 1 )^2 (x^2 + x +  1 )

 

12 tháng 8 2015

a)x4-x3-x+1

=x3(x-1)-(x-1)

=(x-1)(x3-1)

=(x-1)(x-1)(x2+x+1)

=(x-1)2(x2+x+1)

b)5x2-4x+20xy-8y

(sai đề)

 

25 tháng 10 2015

\(a,y-x^2y+2xy^2-y^3=y(1-x^2+2xy-y^2) =y[1-(x^2-2xy+y^2)]=y[1-(x-y)^2] =y(1-x+y)(1+x-y) =y(x+y-1)(x-y+1) \)